The role of rural production cooperatives in improving rural households’ welfare in the Miandoab Township - Kambiz Hassanzadeh; Shahla Choobchian; Esmail Karami dehkordi; Yadgar Momenpor (تعاون و کشاورزی)
Context and purpose: Rural production cooperatives play an important role in sustainable rural development and are one of the advanced stages of cooperation. Rural production cooperatives play a very important role in reducing rural poverty by increasing production efficiency and can provide services that governments are unable to provide for poor people. The purpose of this research was to investigate the role of rural production cooperatives in improving the status of the 12 components of Legatum welfare in rural areas.Methodology/approach. The present research was conducted using a survey and descriptive-correlational methodology. The statistical population of the present study consisted of 17,493 rural household members and non-members in rural production cooperatives of Miandoab city and 377 households were randomly selected. Data were collected through structured interviews and analyzed using SPSS27 and LISREL software 8.8. Findings and conclusions. The results showed that rural production cooperatives play an effective role in improving the 12 structures of Legatum welfare (including safety and security; personal freedom; governance; social capital; investment environment; entrepreneurial conditions; market access and infrastructure; economic conditions; living conditions; health; education and natural environment). Meanwhile, rural production cooperatives played the biggest role in improving the education component. In the end, practical suggestions were presented. Originality. Previous studies have investigated the role of one or two components of welfare, and none of the previous studies have addressed the role of all components of welfare simultaneously, which is considered among the innovations of the current research.